Kierkegaard’s Ideas On Clinical Psychology and Psychotherapy Ana Maria Lopez Calvo de Feijoo & Myriam (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper aims at seeking, in the thought of Søren Kierkegaard, elements to articulate an existential psychology. Through the voice of some of his pseudonyms, Kierkegaard proposes angst and despair as the central themes for a psychological science. These themes provide a place where the vertigo of freedom opens one to the original determination of one's nature, and also a place where a human being can look at and judge himself. Angst and despair appear, to Haufniensis, as the most adequate subjects for a psychological science. We believe that the philosophy of existence, as developed by the Danish philosopher, can provide elements not only for a critique of the psychology of his time, but for the elaboration of a psychology that considers existence in its materiality, leaving behind the belief that human behaviour can be determined by experimental, deductive or metaphysical criteria. In order to do our task we will consider Kierkegaard's thought about the relationship between indetermination and freedom. Afterwards, starting from Haufniensis' considerations about angst as a forming agent, we will consider its implications to the exercise of a clinical psychology with an existential basis. Finally, in order to show the way of this psychology, we will bring a clinical situation with a child.
Keywords: Child clinic; phenomenology; philosophies of existence; indetermination; freedom